ANALISIS PERGESERAN STRUKTUR EKONOMI DAN SEKTOR POTENSIAL DALAM MENDUKUNG PEMBANGUNAN DI KABUPATEN KARANGASEM - Ariani Ni Ketut Ayu; Suyana Utama Made (PIRAMIDA, 2019)
Potential sectors and shift of economic structure in regions have an important role in regional development.Identificationpotential sectors and shift of economic structure, then it could maximize regional development. The study used secondary data from Badan Pusat Statistik Karangasem and Badan Pusat Statistik Bali. The analysis techniques of thisstudy used five techniquessuch as, Shift Share, Locationt Quotient, Dynamic Location Quotient, Growth Ratio Model, Overlay and qualitative analysis.Potential sectors that could support the development in Karangasem regency can be divided into five groups namely the first priority sector (main) is the financial services and insurance sector. Second priority sectors are 1) construction sector, 2) transportation and warehousing sectors, 3) health services sector and social activities. The third priority sector is 1) agriculture, forestry and fishery sector, 2) mining and quarrying sector, 3) processing industry sector, 4) electricity and gas procurement sector, 5) accommodation and drinking sector, 6) real estate sector, 7) government administration, defense and compulsory social security sectors, 8) other service sectors. The fourth priority sector is 1) water procurement sector, waste management, waste and recycling, 2) large and retail trade sector, car and motorcycle repairs, 3) information and communication sector, 4) education services sector and the fifth priority sector corporate services sector.